2022
DOI: 10.3390/ijerph192315535
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Pathogenic Bacteria Strains to Treated Mine Water

Abstract: Mine water as a result of meteoric and/or underground water’s contact with tailings and underground workings could have an elevated content of metals associated with sulfate, often acidic, due to the bio-oxidation of sulfides. When entering aquatic ecosystems, the mine water can cause significant changes in the species’ trophic levels, therefore a treatment is required to adjust the alkalinity and to remove the heavy metals and metalloids. The conventional mine water treatment removes metals, but in many cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…The results showed that Gram-negative bacteria were dominant by 100% in soil samples from Ain Jarura region treated with untreated sulfuric water (WA1, WA2, WA3) (Table-4), as well as for the same soil samples treated with sulfuric water treated with sand filter (GB1), charcoal filter (GB2) and magnetic field filter. (GB3) Soil samples treated with untreated sulfur water were dominated by Pseudomonas aeruginosa with a percentage of 66.7% and Acinetobacter lwoffii with a percentage of 33.3%, The results are in agreement with the findings of a group of researchers in their study, as they found that Pseudomonas aeruginosa was more resistant in the presence of 1890 mg SO4 2-/L [24]. The results showed a change in the bacterial species p. aeruginosa after treating the same soil sample with sulfuric water treated with a charcoal filter, which led to the isolation of the bacterial type Elizabethkingia meningoseptica, and this result indicates the role of the charcoal filter in changing the environment suitable for the growth and dominance of type P. aeruginosa, While the bacterial type P. aeruginosa after treating the same soil sample (from Ain Jarura) with sulfuric water treated with a magnetic field filter.…”
Section: Isolation Of Bacteriasupporting
confidence: 89%
“…The results showed that Gram-negative bacteria were dominant by 100% in soil samples from Ain Jarura region treated with untreated sulfuric water (WA1, WA2, WA3) (Table-4), as well as for the same soil samples treated with sulfuric water treated with sand filter (GB1), charcoal filter (GB2) and magnetic field filter. (GB3) Soil samples treated with untreated sulfur water were dominated by Pseudomonas aeruginosa with a percentage of 66.7% and Acinetobacter lwoffii with a percentage of 33.3%, The results are in agreement with the findings of a group of researchers in their study, as they found that Pseudomonas aeruginosa was more resistant in the presence of 1890 mg SO4 2-/L [24]. The results showed a change in the bacterial species p. aeruginosa after treating the same soil sample with sulfuric water treated with a charcoal filter, which led to the isolation of the bacterial type Elizabethkingia meningoseptica, and this result indicates the role of the charcoal filter in changing the environment suitable for the growth and dominance of type P. aeruginosa, While the bacterial type P. aeruginosa after treating the same soil sample (from Ain Jarura) with sulfuric water treated with a magnetic field filter.…”
Section: Isolation Of Bacteriasupporting
confidence: 89%
“…It can expose residues rich in sulfide minerals to oxidation (Sarker et al, 2023;Wang et al, 2023;Li et al, 2022), which are not economically exploitable and are the overall result of extraction and processing stages (Abdellaoui et al, 2023; Karacan et al, 2023;Araya et al, 2020). The oxidation of these sulfides in tailings under the effect of water and atmospheric oxygen leads to the generation of sulfate-laden acid waters (Bao et al, 2021;Stoica et al, 2022). The latter causes acid mine drainage to occur.…”
Section: Introductionmentioning
confidence: 99%